Estimation and Simulation in Batch Fermentation of Baker's Yeast Production - K. Al-Dawery, Salam; M. Al-Samuray, Abdul-Kahar (Iraqi Journal of Chemical and Petroleum Engineering, 2007)
Baker's Yeast is an important additive among the substances, which improves bred quality, thus, a consideration has been made to study the conditions and parameters that affecting the production of the yeast in a batch fermenter experimentally and theoretically. Experimental runs were implemented in a 12-liter pilot-scale fermenter to predict the rate of growth and other parameters such as amount of additive consumed and the amount of heat generated. The process is modeled and performed using a computer programming prepped for this purpose, the model gave a good agreement comparing to the experimental work specially in the log phase.